Strength Development, Muscle and Tissue Damage in Different Training Models - Akbulut, Taner; Cinar, Vedat; Oner, Salih; Erdogan, Ramazan (Sciencedomain Int, 2021)
Purpose: The aim of this study was to determine the effects of during six weeks core and weight lifting trainings on strength development, muscle and tissue damage which may occur. Method: The research group consisted of sixteen volunteers who participated in the same age group. Participants were divided into two groups, core training group (n: 8) and weight lifting training group (n: 8). Participants continued to the program for the group to which the belonged lasted for three days a week for six weeks. Participant's performance measures (Back and leg strength, hand grip strength, vertical jump) were taken and blood samples were taken twice at rest before and at the end of the training sessions. AST, ALT, LDH, CK and CK-MB levels were determined in the blood samples taken. SPSS 22 package program was used in the analysis of the obtained data. Paired samples t test was used for intra-group comparisons. Results: When intra-group analyses are made; there were significant differences in the leg strength, vertical jump, CK and CK-MB values of the weight lifting training group, it was determined that only differences in back and leg strength values occurred in the core training group(p<0,05). Conclusion: As a result, both core and weight lifting training have led to some improvement in strength parameters. It can be said that especially weight lifting training also causes muscle damage as well as strength development.
16th International Sport Sciences Congress -- OCT 31-NOV 03, 2018 -- Antalya, TURKEY
Keywords: Core; strength training; muscle strength; damage